The risk of cardiorespiratory deaths persists beyond 30 days after proximal femoral fracture surgery. Issue 2 (February 2015) - Khan, Sameer K.; Rushton, Stephen P.; Shields, David W.; Corsar, Kenneth G.; Refaie, Ramsay; Gray, Andrew C.; Deehan, David J.
Abstract: Introduction: 30-day mortality is routinely used to assess proximal femoral fracture care, though patients might remain at risk for poor outcome for longer. This work has examined the survivorship out to one year of a consecutive series of patients admitted for proximal femoral fracture to a single institution. We wished to quantify the temporal impact of fracture upon mortality, and also the influence of patient age, gender, surgical delay and length of stay on mortality from both cardiorespiratory and non-cardiorespiratory causes. Patients and methods: Data were analysed for 561 consecutive patients with 565 fragility type proximal femoral fractures treated surgically at our trauma unit. Dates and causes of death were obtained from death certificates and also linked to data from the Office of National Statistics. Mortality rates and causes were collated for two time periods: day 0–30, and day 31–365. Results: Cumulative incidence analysis showed that mortality due to cardiorespiratory causes (pneumonia, myocardial infarction, cardiac failure) rose steeply to around 100 days after surgery and then flattened reaching approximately 12% by 1 year. Mortality from non-cardiorespiratory causes (kidney failure, stroke, sepsis etc.) was more progressive, but with a rate half of that of cardiorespiratory causes. Progressive modelling of mortality risks revealed that cardiorespiratory deaths were associated with advancing age and male gender ( p  < 0.001 for both), but the effect of age declined after 100 days. Non-cardiorespiratory deaths were not time-dependent. Conclusion: We believe this analysis extends our understanding of the temporal impact of proximal femoral fracture and its surgical management upon outcome beyond the previously accepted standard (30 days) and supports the use of a new, more relevant timescale for this high risk group of patients. It also highlights the need for planning and continuing physiotherapy, respiratory exercises and other chest-protective measures from 31 to 100 days.